Alzheimer's Disease The 21st Century Challenge - Dorszewska, Jolanta; Kozubski, Wojciech (IntechOpen, 2018)
Alzheimer's disease was discovered over 100 years ago and still belongs to incurable neurological diseases; its pharmacotherapy is considered to be ineffective. This book presents contemporary views on the genetic, biochemical, and immunological determinants of this disease. This book also concerns the issue of Alzheimer's disease prevention through lifestyle and physical activity. Moreover, it describes the therapies used in Alzheimer's disease to slow the progression of the disease and delay its onset. Subsequently, the authors discuss experimental and clinical trials used now and in the near future. We hope that this book will help the readers to understand the complex mechanism leading to the development of Alzheimer's disease and indicate effective ways to prevent this disorder.